ANALISIS LAGU ROBO’-ROBO’ KARYA EDDY MAWARDI - Yunisa, Fitri; Syahrani, Agus; Silaban, Chiristianl Yeri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research are to describe the melody of Robo’-Robo’ music, to describe the form of Robo’-Robo’ music melody. The theory that used on this research analysis is the theory about melody, phrase, and music sentence. The method that used in this research is descriptive method. The form of this research is qualitative research. The approach in this research is using musicology approach. The data source in this research is the result from the interviewer that know about the melody and music form of Robo’-Robo’. The data collection tool in this research is the researcher as the main instrument, observation sheet, intervie guide, and documentation. The validity techniques are continous observation and triangulation. The data analysis technique in this research are presenting and then summarize, analyze and interpretation, conclude the analysis result about the melody and music form of Robo’-Robo’ by Eddy Mawardi. Based on the data analysis, we can conclode that the analysis of melody and music form of Robo’-Robo’ the are high and low tone, pattern, tone value and music structure. By the interview with the interviewer who was the musician of Robo’-Robo’ music who also know about the history of Robo’-Robo’ music. Analyze the melody and the music form of Robo’-Robo’ through interview with the interviewer and documenting the melody and music form of Robo’-Robo’. The result of this research was expected can be applied on Seni Budaya SMA Class X Semester II Study and can be reference to advance research abo melody and music form of Robo’-Robo’.Keywords: Robo’-Robo’ Songs, Melody Analysis, Music structure, Musicology